NO2 and natural organic matter affect both soot aggregation behavior and sorption of S-metolachlor. Issue 10 (3rd September 2019) - Sigmund, Gabriel; Castan, Stephanie; Wabnitz, Christopher; Bakkour, Rani; Hüffer, Thorsten; Hofmann, Thilo; Elsner, Martin
Abstract : Transformation of soot with NO2 and interactions with NOM decreased the soot surface charge, size and sorption affinity for organic contaminants. Abstract : Soot is an important carbonaceous nanoparticle (CNP) frequently found in natural environments. Its entry into surface waters can occur directly via surface runoff or infiltration, as well as via atmospheric deposition. Pristine soot is likely to rapidly undergo aggregation and subsequent sedimentation in aquatic environments. Further, soot can sorb a variety of organic contaminants, such as S -metolachlor (log  K D = 3.25 ± 0.12). During atmospheric transport, soot can be chemically transformed by reactive oxygen species including NO2 . The presence of natural organic matter (NOM) in surface waters can further affect the aquatic fate of soot. To better understand the processes driving the fate of soot and its interactions with contaminants, pristine and NO2 -transformed model soot suspensions were investigated in the presence and absence of NOM. NO2 -oxidized soot showed a smaller particle size, a higher number of particles remaining in suspension, and a decreased sorption of S -metolachlor (log  K D = 2.47 ± 0.40). In agreement with findings for other CNPs, soot stability against aggregation was increased for both pristine and NO2 transformed soot in the presence of NOM.